Multidisciplinary Telemedicine Care for Tourette Syndrome: Minireview - Cen, Shan-shan; Yu, Jun; Wang, Qiao; Deeb, Wissam; Wang, Kai-liang; Shukla, Aparna Wagle; Malaty, Irene; Ramirez-Zamora, Adolfo; Zhang, Jian-guo; Hu, Wei; Meng, Fan-gang (Frontiers in Neurology, 2020)
Tourette syndrome (TS) is a chronic neuropsychiatric disorder of childhood-onset characterized by multiple motor and vocal tics. TS poses a considerable burden to both patients and healthcare providers, leading to a major detriment to educational success, occupation, and interpersonal relationships. A multidisciplinary, specialist-driven management approach is required due to the complexity of TS, yet access is dramatically limited, often due to the location of the patient and the geographic clustering of specialists in large urban centers. Telemedicine is the use of electronic information and communication technology to provide and support healthcare when distance separates participants. Therefore, we conducted this mini-review to describe the latest information on telemedicine in the assessment and management of TS and discuss the potential contributions to care for TS patients in a multidisciplinary approach. We believe telemedicine could be a revolutionary method for improving access to patients with TS.